If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -53 + 11x = 57 Reorder the terms: -53 + -6x + 11x = 57 Combine like terms: -6x + 11x = 5x -53 + 5x = 57 Solving -53 + 5x = 57 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + 5x = 57 + 53 Combine like terms: -53 + 53 = 0 0 + 5x = 57 + 53 5x = 57 + 53 Combine like terms: 57 + 53 = 110 5x = 110 Divide each side by '5'. x = 22 Simplifying x = 22
| 2.2(y-11)=0.6-y | | P+4+7p=4 | | 5Y+3.53=22 | | 4x+13x+3x= | | 170t+370=1250 | | x^2+18x+182.25=0 | | 9x^2+12=13 | | 6x/8=54 | | 4.5x=171 | | -27.75=13.5-7.5t | | 7x^2-6=-6 | | 2(-2x+2)=12 | | 8g-4g=28 | | -9=1+4a+6a | | -63+5x-x=21 | | 5x+8=4c | | G(x)=-2x^2-9x+18 | | 2x-8=2x+9 | | -(4x+2)-(-3w-5)=3 | | 0.12(5q-1)-q=0.15(7-2q) | | 10x^2-50=2200 | | 3x+27=2x+20 | | 2x+8=2x+9 | | -396+50x+4x^2=0 | | 2(x-3)+3x=29 | | 3x+7x-6x=14+2 | | -4z=-6z^3-5z^2 | | 2(3x-1)=x+3 | | f(x)=7-7x | | 8x-1=8x^3-1 | | .04(4c-48)=.08(c-6) | | X-6Y+7Z=-9 |